Food and nutrition in numbers 2014 (Food and Agriculture Organization of the United Nations RomeIT, 2014)
Includes detailed food consumption data collected from household budget surveys and comprehensive country and regional profiles with indicators categorised by anthropometry, nutritional deficiencies, supplementation, dietary energy supplies, preceded by their 'setting'.
Keywords: FOOD